Measurement mania : games and activities that make math easy and fun - Long, Lynette (New York : Wiley, 2001)
A collection of educational games and activities designed to help students enjoy and understand the basics of mathematics.
Includes index.
Booklist.
School Library Journal.
Wilson's Children.
4.2.
4.2
Keywords: Measurement -- Juvenile literature; Measurement; Measurement